Droplet Droplet Interactions investigated using a Combination of Electrochemical and Dynamic Light Scattering Techniques: The Case of Water/BHDC/Benzene:n-Heptane System - Florez Tabares, Juan Sebastian (2015)
In this contribution the electrochemistry of [Fe(CN)6]4-/3- as the probe molecule was investigated in benzyl-n-hexadecyldimethylammonium chloride (BHDC) reverse micelles (RMs) varying the composition of the external solvent (benzene:n-heptane mixtures) and the surfactant concentration, at a fixed water content and probe concentration. The electrochemical and dynamic light scattering results show that in water/BHDC/benzene:n-heptane systems the aggregate sizes increase on increasing BHDC concentration. This behavior was unexpected since it is known that for water/BHDC/benzene RM systems keeping the water content constant and the surfactant concentration below 0.2 M, the droplet sizes are independent of the concentration of the surfactant. We explain the results considering that on changing the external solvent to benzene:n-heptane mixtures, RMs tend to associate in clusters and equilibrium between free RMs and droplet clusters is established. A model is presented which, using electrochemical and dynamic light scattering data, allows calculating the aggregation number of the RMs, the number of RMs that form the droplet clusters and the standard electron transfer heterogeneous rate constant.